2014
DOI: 10.1016/j.febslet.2014.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analyses of human gut microbes associated with obesity and IBD

Abstract: Recent studies have linked human gut microbes to obesity and inflammatory bowel disease, but consistent signals have been difficult to identify. Here we test for indicator taxa and general features of the microbiota that are generally consistent across studies of obesity and of IBD, focusing on studies involving high-throughput sequencing of the 16S rRNA gene (which we could process using a common computational pipeline). We find that IBD has a consistent signature across studies and allows high classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
582
6
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 738 publications
(649 citation statements)
references
References 52 publications
56
582
6
5
Order By: Relevance
“…Host genetics and diets have been associated with the shaping of or changes in gut microbiome (26,27). Gut microbes have been identified to be associated with obesity (28). As genetics, dietary habits and BMI vary among different populations, whether the bacterial markers verified in the two Asian cohorts in this study could be applied in other populations needs further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Host genetics and diets have been associated with the shaping of or changes in gut microbiome (26,27). Gut microbes have been identified to be associated with obesity (28). As genetics, dietary habits and BMI vary among different populations, whether the bacterial markers verified in the two Asian cohorts in this study could be applied in other populations needs further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Although an elevated Firmicutes / Bacteroidetes ratio in obese subjects has been reported in multiple studies (Turnbaugh et al ., 2009; Xu et al ., 2012; Bervoets et al ., 2013), a reduced Firmicutes / Bacteroidetes ratio in obese adults has also been found (Schwiertz et al ., 2009). A recent meta‐analysis concluded that there were no statistically significant differences across multiple studies in the Firmicutes / Bacteroidetes ratio between obese and normal‐weight adults (Walters et al ., 2014). In agreement with this meta‐analysis, some pediatric studies have found an increase in Firmicutes and a decrease in Bacteroidetes (Bervoets et al ., 2013; Ferrer et al ., 2013) while others have not (Abdallah Ismail et al ., 2011; Payne et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…7,[26][27][28] These controversial results could be explained by lifestyles, ethnic groups, 29,30 geographic origin 23 and even by the different experimental, bioinformatics and cohort selection methodologies used. 31 Diet is considered a trigger of intestinal microbiota diversity by altering the gut microenvironment. [32][33][34][35] Recently, we reported that gut microbiota, particularly the phylum Firmicutes and a high fat diet increases the chance of developing obesity.…”
Section: Discussionmentioning
confidence: 99%